Pengaruh Jam Kerja dan Kompensasi terhadap Kepuasan Karyawan pada UP Angkutan Sekolah Dishub Provinsi DKI Jakarta - Kurniawan Kurniawan; Natal Indra (Jurnal Bintang Manajemen, 2024)
Human resources play an important role in the future development of the organization. A person works to give his time and energy to the organization as a counter achievement and the organization provides rewards or compensation whose forms can vary greatly. The main key that must be considered by companies in retaining their employees is to prioritize their job satisfaction. Therefore, things that affect the increase in job satisfaction, such as working hours and compensation must be considered. This study aims to analyze the effect of working hours and compensation on employee satisfaction at UP Angkutan Sekolah Dishub DKI Jakarta. The approach used in this research is a quantitative approach with statistical data analysis techniques. The data was collected through distributing questionnaires to 84 employees, and processed using SPSS software version 25. The analysis techniques used include data quality test, classical assumption test, hypothesis testing and coefficient of determination test. The results of this study indicate that partially working hours have no influence and are significant to employee satisfaction, while compensation partially shows that there is an influence and is significant to employee satisfaction. Simultaneously working hours and compensation simultaneously have a positive and significant effect on employee satisfaction.